Psychosocial working conditions and diabetes self-management at work: a qualitative study - Loerbroks, Adrian (Diabetes research and clinical practice, 2018)
Aims - We conducted a qualitative study to expand our current understanding of the potential link between psychosocial working conditions and diabetes self-management at work. - Methods - Thirty employed adults with diabetes mellitus living in Germany (n=19 with type 1, n=11 with type 2, 57% female, aged 24-64years) were recruited. Using a topic guide, we carried out in-depth interviews in face-to-face contact or by telephone. Interviews were transcribed and content-analyzed using MaxQDA. - Results - Psychosocial working conditions perceived to detrimentally affect self-management activities included, amongst others, a high workload, poor job control, unhygienic working environments, the requirement to work under high or fluctuating temperature, perceived social norms at the workplace, and the attitude to prioritize work-related demands as opposed to diabetes-related demands. The types of self-management activities considered to be adversely affected related to glucose monitoring, insulin injections, dietary control, the ability to recognize hypoglycemia and health care use. - Conclusions - Various types of occupational psychosocial factors may determine diabetes self-management practices at the workplace. Quantitative studies are needed to confirm our observations. Subsequently, interventions could be developed and evaluated to improve opportunities to adequately engage into diabetes self-management at work.